The association between self-rated health and mortality in different socioeconomic groups in the GAZEL cohort study - Singh-Manoux, Archana (Oxford University Press, 2007)
OBJECTIVES: Self-rated-health (SRH) is considered a valid measure of health status as it has been shown to predict mortality in several studies. We examine whether SRH predicts mortality equally well in different socioeconomic groups. METHODS: Data (14879 men and 5525 women) are drawn from GAZEL, a prospective cohort study of French public utility workers. Data on SRH and the socioeconomic measures (education, occupational position and income) were taken from the baseline questionnaire (1989), when the average age of individuals was 44.2 years (SD = 3.5). Mortality follow-up was available for a mean of 17.2 years and analysed over the first 10 years and over the entire follow-up period. Associations between SRH and mortality were assessed using Cox regression models using the Relative Index of Inequality (RII) to summarize associations. RESULTS: The RII for the association between SRH and mortality over the first 10 years was 6.78 (95% confidence interval (CI)=3.33–13.81) in the lowest occupational group and 2.10 (95% CI = 0.97–4.54) in the highest. For income, the RIIs were 8.82 (95% CI=4.70–16.54) for the lowest and 1.80 (95% CI=0.86–3.80) for the highest groups respectively. Findings over the full follow-up period were similar. The association between SRH and mortality was weaker in the high occupation and income groups, both in the short and the long term. The results for education were similar but generally weaker than for the other socioeconomic measures. CONCLUSIONS: The predictive ability of SRH for mortality weakens with increasing socioeconomic advantage among middle-aged individuals. Thus SRH appears not to measure “true” health status in a similar way across socioeconomic categories.